Etika Kelompok dalam Konseling - Azmi, Fadia Nurul; Syarqawi, Ahmad (VISA: Journal of Vision and Ideas, 2024)
Literature study is a way to obtain information or references about research subjects. After that, the data was examined using descriptive analysis. The descriptive analysis method begins with an in-depth explanation of the facts. Furthermore, this analysis goes beyond simple explanations to include adequate understanding and sound reasoning. Improving the understanding and application of ethics in group counseling requires collective efforts from various parties. Recommendations that can be implemented include standardizing ethics education and training, ongoing ethics training, developing ethical resources, increasing the role of supervisors, strengthening ethical culture in organizations, and increasing awareness of group members.